Antibody Engineering Volume 1 - Kontermann, Roland E.; Kontermann, Roland E.; Dübel, Stefan.; Dübel, Stefan. (Springer Protocols Handbooks,, 2010)
Antibodies are indispensable tools for research, diagnosis, and therapy. Recombinant approaches allow the modification and improvement of nearly all antibody properties, such as affinity, valency, specificity, stability, serum half-life, effector functions, and immunogenicity. Antibody Engineering provides a comprehensive toolbox covering the well-established basics but also many exciting new techniques. The protocols reflect the latest "hands on" knowledge of key laboratories in this still fast-moving field. Newcomers will benefit from the proven step-by-step protocols, which include helpful practical advice; experienced antibody engineers will appreciate the new ideas and approaches. The book is an invaluable resource for all those engaged in antibody research and development.